Pata-Type Fixed-Point Theorems in Kaleva–Seikkala’s Type Fuzzy Metric Space - Ao-Lei Sima; Fei He; Ning Lu (Journal of Function Spaces)
The purpose of this paper is to generalize the fixed-point theorems for Banach–Pata-type contraction and Kannan–Pata-type contraction from metric spaces to Kaleva–Seikkala’s type fuzzy metric spaces. Moreover, two examples are given for the support of our results.